Thermal degradation of bonding strength of aspen plywood : Toplinska degradacija čvrstoće lijepljenja ploče od uslojenog drva jasike - Bekhta, Pavlo (Array, 2020)
The objective of this research was to study the effect of exposure time on the bonding strength of aspen plywood at elevated temperatures. The plywood samples were manufactured under laboratory conditions using two types of adhesive: urea-formaldehyde (UF) and phenol-formaldehyde (PF). The plywood samples were tested after exposure to three different temperatures (150 °C, 200 °C and 250 °C) and three exposure time levels (1, 2 and 3 hours) at each temperature. Additionally, a set of control samples was tested at room temperature. The quality of bonding was assessed by shear strength test in compliance with the requirements of the standard EN 314-1. The mass and density losses as well as colour changes of the plywood samples were also determined. The findings of this study indicated that exposure of plywood panels to elevated temperature caused significant degradation of their bonding strength. PF plywood samples lost 63.2 % of their initial strength after 3 h of exposure at 250 °C, while UF samples lost 65.9 % of their initial strength already after 3 h of exposure at the temperature of 200 °C. Statistical regression-based models were also developed for predicting the loss of plywood bonding strength as functions of mass and density losses and total colour difference. As the mass/density losses or total colour difference of panels increased, the losses in bonding strength increased too.